Two exceptionally preserved biotas from North Dakota reveal cryptic Ordovician shelf ecologies - Giovanni Mussini; Nicholas J. Butterfield (Proceedings of the National Academy of Sciences, 2025)
The Ordovician saw one of the greatest evolutionary radiations in the Earth’s history, precipitating the assembly of modern animal-dominated ecologies in the aftermath of the Cambrian Explosion. However, Ordovician nonmineralized faunas are rare and mostly sample ecologically marginal settings. We describe small carbonaceous fossils (SCFs), including semiarticulated elements preserving submicrometric detail, from epicratonic deposits of the Deadwood and Winnipeg formations (ND). The Osterberg SCFs, associated with biostratigraphically informative conodonts and graptolites, record two successive biotas of Cambrian-Tremadocian (the “lower Osterberg” biota) and Darriwilian (the “upper Osterberg” biota) ages, demonstrating a long-term persistence of high-quality, Burgess Shale-type microfossil preservation after the end of the Cambrian. Their components open a window on normal marine, well-oxygenated Ordovician shelf habitats, revealing taxa and functional morphologies unrecorded by coeval macrofossils. These include specialized grazing and predatory molluskan radulae, triturative crustaceomorph molars, the oldest known eurypterid-type cuticles, and microphagous priapulid worms. The Osterberg fossils attest to an Ordovician co-occurrence of cryptic taxa and feeding adaptations, reminiscent of the most ecologically modern Cambrian biotas, alongside classic later-Paleozoic forms like colonial zooplankton and biomineralized early vertebrates. By contrast, they do not record classic Burgess Shale-style taxa typical of marginal or deeper-water Ordovician assemblages. These results demonstrate a lasting presence of cryptic, modern-style shelf faunas throughout the earliest Paleozoic, suggesting that exceptional Ordovician macrofossil sites are unrepresentative of the broader state of their coeval biosphere.